The Production of Lightweight Aggregates from Local Wastes - Khairul Nizar, Ismail, Dr.; Mohd Sobri, Idris; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Sabarudin, Mohd; Khairun Azizi, Mohd Azizli (Polish Association of Inventors and Rationlizers, 2010)
Dr. Khairul Nizar Ismail and his team won gold at International Warsaw Invention Show (IWIS), 30th - 31st May 2007 at Warsaw, Poland.